1985
DOI: 10.1111/1523-1747.ep12276826
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Body-Enriched Fractions from Neonatal Mice: Preparative Techniques and Partial Characterization

Abstract: Several problems have frustrated the isolation of lamellar bodies (LB) from mammalian epidermis. We obtained pellets enriched in intact LB by utilizing the staphylococcal epidermolytic toxin to provide intact, outer epidermal sheets, by controlled homogenization in a cell disrupter, and by passage of homogenates through a graded series of nuclepore filters (Science 221:962, 1983). Such preparations contained more intact LB than did fractions prepared by a variety of differential or sucrose/metrizamide disconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
119
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(123 citation statements)
references
References 33 publications
3
119
0
1
Order By: Relevance
“…2130 a major site of steroidogenesis, 20 and 15-30% of the mass of epidermal lamellar bodies is composed of sterols or their derivatives. 31 - 32 As expected from these observations, disruption of the murine epidermal permeability barrier leads to increased keratinocyte sterol synthesis during barrier recovery. 33 - 35 In addition, certain epidermal alterations (neutral lipid storage disease and essential fatty acid deficiency) are characterized by keratinocyte hyperproliferation, increased levels of corneocyte desquamation, and breakdown of the epidermal permeability barrier.…”
Section: Discussionsupporting
confidence: 53%
“…2130 a major site of steroidogenesis, 20 and 15-30% of the mass of epidermal lamellar bodies is composed of sterols or their derivatives. 31 - 32 As expected from these observations, disruption of the murine epidermal permeability barrier leads to increased keratinocyte sterol synthesis during barrier recovery. 33 - 35 In addition, certain epidermal alterations (neutral lipid storage disease and essential fatty acid deficiency) are characterized by keratinocyte hyperproliferation, increased levels of corneocyte desquamation, and breakdown of the epidermal permeability barrier.…”
Section: Discussionsupporting
confidence: 53%
“…LGs are a major source of stratum corneum lipid precursors and various hydrolytic enzymes such as lipases, proteases, acid phosphatases, and glycosidases (27,29,30) and other proteins including corneodesmosin (31). Among lysosomal glycoproteins identified in this study, glucosylceramidase and cathepsin D have been reported to be present in LGs (29,31).…”
Section: Table I Observed Signals Of Aowr-labeled Oligosaccharides Rementioning
confidence: 57%
“…Among lysosomal glycoproteins identified in this study, glucosylceramidase and cathepsin D have been reported to be present in LGs (29,31). Although further investigation is required, the high abundance of high mannose type oligosaccharides observed in epidermis may be attributable to the striking roles of lysosomal enzymes and/or the high abundance of lamellar granule in epidermis.…”
Section: Table I Observed Signals Of Aowr-labeled Oligosaccharides Rementioning
confidence: 68%
“…6) rather than into broad continuous lamellar bilayer unit structures. However, a failure to process lamellar body contents after secretion is likely to be too simplistic an interpretation for these observations because stratum corneum of 19-d pups was not enriched in glycosphingolipids or phospholipids as one would predict for unprocessed lamellar body-derived lipids (23,24). Coincident with establishment of a functional bamer, the quantity of lipid per unit area of stratum corneum increased -2-fold (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Lamellar bodies are enriched in phospholipids, free sterols, glucosylceramides, and a selected complement of hydrolytic enzymes, including lipases, glycosidases, and proteases (22)(23)(24)(25). Upon secretion of lamellar body contents at the stratum granulosum/stratum corneum interface, these enzymes apparently convert the polar lipids and glycosphingolipids to neutral lipids and ceramides.…”
mentioning
confidence: 99%